Anorexia and the Refusal of Medical Treatment - Oliver, J (Victoria University of Wellington Law Review, 1997)
The Bill of Rights Act 1990 gives everyone the right to refuse medical treatment. In Re CMC, the right of an anorexic patient to refuse treatment was overridden by the Family Court. Anorexia nervosa is recognised as a mental illness which predominantly affects women. This article considers the philosophical and legal basis for that decision. The writer also touches on the wider ethical and social issues raised by the decision.